Preconception malnutrition among women and girls in south Asia: prevalence, determinants, and association with pregnancy and birth outcomes - Faith Miller; Vani Sethi; Danielle Schoenaker; Ranadip Chowdhury; Raj Kumar Verma; Jane Hirst; Manisha Nair; Chiara Benedetto; Usha Sriram; Zivai Murira; Naomi M. Saville (The Lancet Regional Health - Southeast Asia)
Summary: This review highlights the growing double burden of malnutrition among women of reproductive age in South Asia. Using nationally-representative survey data, we highlight that the prevalence of overweight now exceeds that of underweight, while anaemia remains persistently high despite intervention efforts. Underweight and anaemia are more common among unmarried women, whereas overweight is more prevalent among parous women, underscoring the need for life-stage-specific preconception nutrition programs. In our systematic review, micronutrient deficiencies vary widely between and within countries, reflecting regional disparities in nutritional status and inconsistencies in diagnostic methods. Associations of preconception underweight, overweight, anaemia and micronutrient deficiencies with health, nutrition, socio-demographic, and WASH indicators are mixed, emphasising the need for tailored, context-specific interventions. The lack of longitudinal studies limits our understanding of associations between preconception nutritional status and subsequent birth outcomes, underscoring the need for comprehensive, longitudinal studies across South Asia to inform and monitor targeted nutrition programs.